Serotonin: biological properties and its receptors - Akhmetova М. Zh.; Tykezhanova G.М.; Mindubaeva F.А.; Nigmatullina, R.R. (Fundamental and Experimental Biology, 2019)
In the last decade, much attention has been paid to the study of the serotonergic system. The molecular and cellular mechanisms of the synthesis of serotonin, its metabolism and receptor interaction are well studied. The wide range of serotonin effects is explained by the presence of a wide variety of serotonin receptors. The serotonin (5-hydroxytryptamine, 5-HT) is the main mediator of the serotonergic system. In human the role of 5-HT in the central nervous system (CNS) is best characterized, where the amine remain in force as a neuro-transmitter in neural synapses and participates in the formation and regulation of various physiological functions of the body in normal conditions and in pathology, playing a role in maintaining homeostasis. 5-HT is a neurohormone that has a morphogenetic and regulatory effect on target organs, including the heart and blood vessels. The serotonergic system is a link in the pathogenesis of atherosclerosis, arterial and pulmonary hypertension, coronary heart disease, atrial fibrillation and heart failure. In patients with coronary heart disease an increase serotonin concentration in the blood was found. The effect of the serotonergic system on the car-diovascular system has been studied quite thoroughly inanimals. Serotonin has been shown to have a positive inotropic effect on the myocardium ofthe atria and ventricles of variousmammals. Also, the neurotransmitter serotonin plays an important role in the formation of the brain. Low levels of serotonin in the initial stages of development will lead to the fact that the adult brain will inadequately process sensory signals. The review covers the significance and a wide range of biological effects of serotonin in the central nervous system and outside the central nervous system, which is explained by the diversity of the 5-HT receptor family.